2018
DOI: 10.1002/1873-3468.13047
|View full text |Cite
|
Sign up to set email alerts
|

Refolding of helical soluble α‐synuclein through transient interaction with lipid interfaces

Abstract: α-Synuclein (αSyn) is a key player in the pathogenesis of Parkinson's disease and other synucleinopathies. Here, we report the existence of a novel soluble α-helical conformer of αSyn, obtained through transient interaction with lipid interfaces, and propose dynamic oligomerization as the mechanism underlying its stability. The conformational space of αSyn appears to be highly context-dependent, and lipid bilayers might thus play crucial roles as molecular chaperones in a cellular environment.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…In such a dynamic equilibrium, αS is expected to efficiently shuttle between cytosol and membranes, i.e., it constantly binds to and gets released from lipid bilayers. Transient interactions of αS monomers with membranes may drive multimerization ( Dettmer et al, 2016 , 2017 ), something that recently was observed in an in vitro helical αS (tetramer) reconstitution system ( Rovere et al, 2018 ). A possible scenario is that the induced amphipathic αS helices at lipid bilayers may over time cooperatively interact with each other in such a way that the hydrophobic portions of four monomers face each other, resulting in tetramer/multimer formation and simultaneous release from membranes.…”
Section: αS Multimerizationmentioning
confidence: 90%
See 2 more Smart Citations
“…In such a dynamic equilibrium, αS is expected to efficiently shuttle between cytosol and membranes, i.e., it constantly binds to and gets released from lipid bilayers. Transient interactions of αS monomers with membranes may drive multimerization ( Dettmer et al, 2016 , 2017 ), something that recently was observed in an in vitro helical αS (tetramer) reconstitution system ( Rovere et al, 2018 ). A possible scenario is that the induced amphipathic αS helices at lipid bilayers may over time cooperatively interact with each other in such a way that the hydrophobic portions of four monomers face each other, resulting in tetramer/multimer formation and simultaneous release from membranes.…”
Section: αS Multimerizationmentioning
confidence: 90%
“…It is tempting to speculate that membrane-enriched αS variants such as KLK and EIV might even help stabilize αS multimers in vitro if we found methods and conditions to release membrane-enriched αS variants from membranes while the hydrophobic faces of their amphipathic helices engage in ordered synuclein-synuclein interactions at the same time. This approach, of course, would only be valid if the mechanism that drives wt αS multimerization in vivo is sufficiently similar to this scenario, for which there is some evidence ( Wang et al, 2011 ; Gurry et al, 2013 ; Rovere et al, 2018 ).…”
Section: αS Multimerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, small vesicles with loosely packed membranes facilitate the binding of α-Syn ( Nuscher et al, 2004 ). Notably, a recent study suggests a soluble helical multimer formation of α-Syn when released from the membrane ( Rovere et al, 2018 ).…”
Section: Alpha-synuclein Interaction With Membrane Phospholipidsmentioning
confidence: 99%
“…These two mechanisms are not mutually exclusive and should be studied as two sides of the same coin. In fact, amyloid formation can be catalyzed by vesicle binding (12), and membrane interactions are important for the formation of aggregation-resistant forms of α-Syn (13,14). And while a recently published PD mouse model with a strong neurodegenerative and movement disorder phenotype had α-Syn-positive inclusions rich in vesicle clusters in young mice, older animals seemed to have more classical amyloid aggregates (15).…”
mentioning
confidence: 99%